Lycopene Inhibits Propagation of Chlamydia Infection - Naylia A. Zigangirova; Elena Y. Morgunova; Elena D. Fedina; Natalia V. Shevyagina; Tatiana G. Borovaya; Vladimir G. Zhukhovitsky; Nigel H. Kyle; Ivan M. Petyaev (Scientifica)
Chlamydiaceae is a family of obligate intracellular pathogenic bacteria with similar developmental cycles and cell biology responsible for a wide range of diseases in different hosts including genital and eye inflammatory diseases, arthritis, and inflammatory diseases of the respiratory and cardiovascular systems. In the present paper, we report that lycopene, one of the main dietary carotenoids, which is present in tomato and some other fruits, has a strong inhibitory effect on C. trachomatis and C. pneumoniae infections in alveolar macrophages. This finding was documented by both immunofluorescence analysis and electron microscopy. It was noted that lycopene treatment inhibited intracellular phase of the chlamydial developmental cycle and resulted in a significant loss of infectious progeny. The antichlamydial effect of lycopene was also confirmed in a clinical setting. There was a significant reduction of IgG antibodies against C. pneumoniae in the serum of volunteers treated for a month with oral ingestion of 7 mg of lycopene. Additional studies are needed to further explore the antichlamydial activity of lycopene and its possible effect on C. pneumoniae in relation to antichlamydial activity of lycopene to mechanisms of atherosclerosis.